Applying User-Centered Design Methods to the Development of an mHealth Application for Use in the Hospital Setting by Patients and Care Partners - Couture, Brittany; Lilley, Elizabeth; Chang, Frank; DeBord Smith, Ann; Cleveland, Jessica; Ergai, Awatef; Katsulis, Zachary; Benneyan, James; Gershanik, Esteban; Bates, David W.; Collins, Sarah A. (Applied Clinical Informatics, 2018)
Introduction Developing an optimized and user-friendly mHealth application for patients and family members in the hospital environment presents unique challenges given the diverse patient population and patients' various states of well-being.Objective This article describes user-centered design methods and results for developing the patient and family facing user interface and functionality of MySafeCare, a safety reporting tool for hospitalized patients and their family members.Methods Individual and group usability sessions were conducted with specific testing scenarios for participants to follow to test the usability and functionality of the tool. Participants included patients, family members, and Patient and Family Advisory Council (PFAC) members. Engagement rounds were also conducted on study units and lessons learned provided additional information to the usability work. Usability results were aligned with Nielsen's Usability Heuristics.Results Eleven patients and family members and 25 PFAC members participated in usability testing and over 250 patients and family members were engaged during research team rounding. Specific themes resulting from the usability testing sessions influenced the changes made to the user interface design, workflow functionality, and terminology.Conclusion User-centered design should focus on workflow functionality, terminology, and user interface issues for mHealth applications. These themes illustrated issues aligned with four of Nielsen's Usability Heuristics: match between system and the real world, consistency and standards, flexibility and efficiency of use, and aesthetic and minimalist design. We identified workflow and terminology issues that may be specific to the use of an mHealth application focused on safety and used by hospitalized patients and their families.
Keywords: user-centered design; patient safety; patient- and family-centered care; mHealth